Community Empowerment and Symbolic Messages of the Pemung Bangen Lepa Ajau Traditional Ceremony in Teras Nawang Village - Prihastuti, Wahyaning (Pusat Studi Pembangunan dan Pemberdayaan, 2024)
The tradition of traditional ceremonies that are always carried out in a society is an ancestral heritage that is given or transmitted from generation to generation. In this case, the community receives various messages from their ancestors through the traditional ceremony. As we can see in a traditional ceremony of a post-harvest party in Teras Nawang village, Bulungan district, North Kalimantan Province. Pemung Bangen Leppa Ajau is a traditional tradition of the Dayak Kenyah Lepu’ Tau tribe which is one of the indigenous tribes in Bulungan Regency, North Kalimantan Province. The Pemung Bangen Lepa’ Ajau Traditional Ceremony contains symbolic messages that are depicted in the 4 elements in the Traditional Ceremony. The decorative elements and ornaments in the Lamin Customary Hall of Uyau I’ot. These decorations and ornaments provide symbolic messages of life for the community. The second element is the Dance performed in the Pemung Bangen Lepa’ Ajau Traditional Ceremony. The third element is the Communal Pre-Event Activities and Traditional Food. The fourth element is the traditional clothing used in the Pemung Bangen Lepa’ Ajau Traditional Ceremony. These four elements are important points in Pemung Bangen Lepa’ Ajau. Through these elements, the community will gain a cultural experience that implies symbolic messages in the procession of the ceremony.